The Action Verbanalysis In The Legend Of Putri Hijau Comic Text - Simamora, Nabilah Khalisah Boru (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
This study deals with the analyzing of action verb in The Legend of Putri Hijau Comic Text. This study is conducted to analyzed types of action verb to find outthe dominate types of action verb in The Legend of Putri Hijau Comic Text. This research used the qualitative descriptive method. The types of action verb divided into 5 types of action verb: transitive verb, transitive active verb, transitive passive verb, intransitive verb, and intransitive complete verb.The researcher have found the result the data that the type of action verbin transitive verb were48 action verbs in transitive verbs type, 6 action verbs were found in transitive active verbs type, 7 action verbs were found in transitive passive verbs types, 3 action verbs were found in intransitive verb types,and 7action verbs were found in intransitive complete verb. The total all were 71 action verbs in The Legend of Putri Hijau comic text.Types of action verb that were dominated from the five types of action verb were action verb type transitive verb.